2014
DOI: 10.4055/cios.2014.6.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction after Arthroscopic Repair of Acetabular Labral Tears

Abstract: BackgroundAcetabular labral tear is a main cause of hip pain and disability, often requiring surgical treatment. Improvements of hip arthroscopic technique have produced positive outcomes after labral repair with arthroscopy. The purpose of this study was to determine clinical outcomes and patient satisfaction after arthroscopic repair of acetabular labral tear.MethodsWe interviewed 21 patients (10 men and 11 women; mean age, 36 years [range, 22 to 57 years]) with acetabular labral tears that had been repaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Numerous publications have documented the outcomes of hip arthroscopy in patient cohorts aged younger than 50 years, with positive patient-reported outcomes (PROs) at 2 and 10 years; however, limited research exists regarding the outcomes of hip arthroscopy in elderly patients. [2][3][4][5][6][7][8] A literature search yielded 2 publications that specifically focused on PROs after hip arthroscopy in patients older than 50 years. 9, 10 Philippon et al 10 evaluated a cohort of patients aged 50 years or older undergoing arthroscopic surgery for femoroacetabular impingement and found that patients with less than 2 mm of joint space had a high risk of early conversion to total hip arthroplasty (THA).…”
mentioning
confidence: 99%
“…Numerous publications have documented the outcomes of hip arthroscopy in patient cohorts aged younger than 50 years, with positive patient-reported outcomes (PROs) at 2 and 10 years; however, limited research exists regarding the outcomes of hip arthroscopy in elderly patients. [2][3][4][5][6][7][8] A literature search yielded 2 publications that specifically focused on PROs after hip arthroscopy in patients older than 50 years. 9, 10 Philippon et al 10 evaluated a cohort of patients aged 50 years or older undergoing arthroscopic surgery for femoroacetabular impingement and found that patients with less than 2 mm of joint space had a high risk of early conversion to total hip arthroplasty (THA).…”
mentioning
confidence: 99%
“…However, the unstable type of acetabular labral tears is generally uncommon. 9 Fourth, like pincer-type FAI, most labral tears in the HL group were the peripheral longitudinal type (Lage type 3) or the more advanced, unstable type (Lage type 4). In previous studies, type 4 was uncommon in normal-sized labral tears.…”
Section: Discussionmentioning
confidence: 91%
“…Although many studies on arthroscopic repair of acetabular labral tears have consistently reported encouraging results at the short- to midterm follow-up, most cases were combined with bony structural abnormalities. 2,9,20,25 Because isolated acetabular labral tears rarely occur and are frequently associated with structural osseous abnormalities, such as cam-type and/or pincer-type FAI lesions, 1 the treatment of isolated acetabular labral tear is seldom reported. Schilders et al 22 compared arthroscopic labral repair (69 hips) and resection (32 hips) in 96 patients (101 hips) at a mean follow-up of 2.4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, these conditions are managed arthroscopically with relatively high rates of reported patient satisfaction. 95,96 Recent data have shown that outcomes of labral repair during FAI surgery are superior to labral debridement procedures. 97,98 The role of labral reconstruction is unclear and further study is needed.…”
Section: Labral Tears Chondral Damage and Loose Bodiesmentioning
confidence: 99%